Predictors of Membership in Alcoholics Anonymous in a Sample of Successfully Remitted Alcoholics - Krentzman, Amy R. (2011)
This study identifies factors associated with Alcoholics Anonymous (AA) membership in a sample of 81 persons who have achieved at least one year of total abstinence from drugs and alcohol. Forty-four were AA members, 37 were not. Logistic regression was used to test the cross-sectional associations of baseline demographic, substance-related, spiritual and religious, and personality variables with AA membership. Significant variables from the bivariate analyses were included in a multivariate model controlling for previous AA involvement. Having more positive views of God and more negative consequences of drinking were significantly associated with AA membership. This information can be used by clinicians to identify clients for whom AA might be a good fit, and can help others overcome obstacles to AA or explore alternative forms of abstinence support.